2013
DOI: 10.1177/0883073813499610
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Influenza

Abstract: We report on a child with mild encephalopathy with reversible splenial lesion (MERS) associated with influenza infection and present a case series of neurological complications associated with influenza infections in children who presented to a tertiary children's hospital in Australia over a period of one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
4
7
0
Order By: Relevance
“…In our study, laboratory data did not show any significant alteration either when the whole study group was observed, or when the cohort was divided into the two different age groups, as reported in available literature [2,[5][6][7][8]19,24].…”
Section: Discussionsupporting
confidence: 69%
“…In our study, laboratory data did not show any significant alteration either when the whole study group was observed, or when the cohort was divided into the two different age groups, as reported in available literature [2,[5][6][7][8]19,24].…”
Section: Discussionsupporting
confidence: 69%
“…In our study, laboratory data did not show any significant alteration either when the whole study group was observed, or when the cohort was divided into the two different age groups, as reported in available literature [2,[5][6][7][8]19,24].…”
Section: Discussionsupporting
confidence: 69%
“…This clinicoradiological syndrome is termed ‘mild encephalitis/encephalopathy with reversible splenial lesion’ (figure 2). 10 Another pattern associated with influenza and other infections manifests as bilateral necrosis of the thalami and other regions, including the brainstem, cerebellum and cerebral white matter 8. This syndrome is termed ‘acute necrotising encephalopathy’ and has a more severe clinical course and worse prognosis.…”
Section: Neurological Conditions That Mimic Infectious Encephalitismentioning
confidence: 99%